Dichotic listening training in children with autism spectrum disorder: A single subject design. (2nd December 2015) - Denman, Inga; Banajee, Meher; Hurley, Annette
Abstract: Objective : Previous research has shown that dichotic listening training has improved auditory and language processing for individuals with large interaural asymmetries on dichotic listening tasks. This training can be a useful treatment for children with autism spectrum disorder (ASD). Design : A single subject, multiple baseline across subjects study was utilized. Study sample : Three children with ASD, between the ages of 8–12, participated in the study. Results : This training demonstrated improvement in language and auditory processing tasks following completion of up to twelve weeks of auditory training. Conclusion : This study supports the idea that deficit specific, dichotic auditory training can remediate auditory and language deficits for children with ASD. More research is needed, with a group design and controls, in order to generalize these results to the larger ASD population.